2022
DOI: 10.3390/biom12050661
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Therapy Improves Parkinson’s Disease by Promoting Mitochondrial Biogenesis via the SIRT-1/PGC-1α Pathway

Abstract: Hyperbaric oxygen therapy (HBOT) has been suggested as a potential adjunctive therapy for Parkinson’s disease (PD). PD is a neurodegenerative disease characterized by the progressive loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc). The aim of this study was to investigate the protective mechanisms of HBOT on neurons and motor function in a 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse model of PD and 1-methyl-4-phenylpyridinium (MPP+)-mediated neurotoxicity in SH-SY5Y cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…It can be suggested that activation of autophagy contributes to the alleviation of PD by regulating VDAC1; however, there is no VDAC1-specific autophagy activator. Studies on PD patients, research by Chu et al, and our current study have shown that VDAC1 expression is downregulated during PD [60], but VDAC1 expression is not downregulated in vivo and in vitro models of PD [41,42,59,[78][79][80][81]. We speculate that VDAC1 may be a double-edged sword playing different roles in PD.…”
Section: Limitationssupporting
confidence: 49%
See 1 more Smart Citation
“…It can be suggested that activation of autophagy contributes to the alleviation of PD by regulating VDAC1; however, there is no VDAC1-specific autophagy activator. Studies on PD patients, research by Chu et al, and our current study have shown that VDAC1 expression is downregulated during PD [60], but VDAC1 expression is not downregulated in vivo and in vitro models of PD [41,42,59,[78][79][80][81]. We speculate that VDAC1 may be a double-edged sword playing different roles in PD.…”
Section: Limitationssupporting
confidence: 49%
“…In mammals, there are three isoforms of VDACs, namely, VDAC1, VDAC2, and VDAC3 [ 40 ]. Previous studies on animal models of PD have reported that expression of VDACs has shown significant modification and is closely related to mitochondrial function [ 41 , 42 ]. VDACs mainly participate in cell energy metabolism by affecting the transport of adenosine triphosphate (ATP) or adenosine diphosphate (ADP) inside and/or outside the mitochondria [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…A grip strength meter (Bio-GS3, BioSeb, Vitrolles, France) was used to evaluate the muscle strength of the whole limb muscle force; the grip strength test of the mice was conducted following the methodology described in our previous reports [ 71 , 72 , 73 ] and research reports from other labs [ 74 , 75 ]. Before the experiment, mice were acclimated to the new environment for 2 h. For each trial, mice were placed on the grid of the device and pulled parallel to the ground at a constant speed until loss of grip and the maximum force generated just before the mouse lost its grasp was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The open-field test was used to measure locomotor activity and anxiety-like behavior [ 40 , 72 , 77 ]. The apparatus is composed of a chamber (50 × 50 cm in diameter, 25 cm in height).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have shown that inhibiting SIRT-1 affects neural plasticity, gene expression, mitochondrial dysfunction, and inflammation [ 11 , 12 ]. Decreased SIRT-1 function and associated causes are responsible for Alzheimer's disease (AD) [ 13 ], schizophrenia [ 14 ], Parkinson's disease (PD) [ 14 , 15 ], and multiple sclerosis (MS) [ 16 , 17 ]. Consequently, SIRT-1 downregulation in specific brain regions can result in ALS-like symptoms.…”
Section: Introductionmentioning
confidence: 99%